Field evaluation of different economic threshold levels for chemical control of pink bollworm (Pectinophora gossypiella), spotted bollworm (Earias vittella, E. insulana) and cotton bollworm (Helicoverpa armigera) on cotton (Gossypium species) - SIMWAT, G S; DHAWAN, A K (The Indian Journal of Agricultural Sciences, 2013)
Â An experiment was conducted during 1993-95 for testing the performance of different economic threshold levels for controlling bollworms [Pectinophora gossypiella (Saund.), Earias vittella (Fabr.), E. insulana (Boisd.)J and cotton bollworm [Helicoverpa armgera (Hubner)] with insecticides. These economic thresholds included 5% bollworm incidence in intact floral formS on the plants and 5, 10 and 15% bollworm incidence in the shed floral forms, and they were compared with standard spray schedule. Varieties ’LH 900’, ’LH 1134’ and ’F 846’ of upland cotton (Gossypium hirsutum L.) and ’LD 327’ of tree cotton (Gossypium arboreum L.) were used. The comparative performance of these treatments was assessed by observing bollworm incidence in open bolls and recording yield of seed cotton. The pooled analysis of data (1993-94) showed that bollworm incidence in open bolls, both on boll and locule basis, was significantly higher at 5% bollworm incidence in intact floral forms than 5 and 10% bollworm incidence in shed floral forms and standard spray schedule. But the yield of seed cotton in the former, which was on a par with that of standard spray schedule, was significantly higher than 5 and 10% bollworm incidence in shed floral fOfms. The cost: benefit rariq was also highestÂ Â Â Â (1Â· : 26.29) in 5% bollworm incidence in intact floral fonns. The pooled analysis of data (1995) revealed that the. performance of all economic threshold levels including standard spray schedule was ana par with each other regarding boll damage (8.2-10.3%), locule damage (4.3-S.6%) in open bolls and yield of seed cotton (1 490-1 678 kg/ha). The cost: benefit ratio was, however, highest in standard spray schedule (1 : 9.54), followed by 5% bollworm incidence in intaet rioral forms (1 : 7.20), 15% (1 : 6.28), 10% (1 :.5.79) and 5% (1 : 5.51) bollworm incidence in shed floral forms.